Potential Economic Losses Due to Tidal Inundation and Flood at Semarang City - Suhelmi, Ifan R; Fahrudin, Achmad; Triwibowo, Ferdinand Hariyanto (Universitas Muhammadiyah Surakarta, 2014)
Coastal city of Semarang is susceptible to the impact of coastal hazard due to its flat topographic condition. Various environmental problems are faced by Semarang involve tidal inundation, land subsidence, and floods during rainy season. This study was conducted to examine the potential economic losses caused by the sea level rise phenomenon. Distribution of inundated area mapped using Digital Elevation Model and Land Subsidence data. The Scenarios of International Panel on Climate Change (2007) sea level rises used to build a model of inundated area that notes by 2030 the rise of sea level rise at 13.4 cm. The inundated map was overlayed with landuse map to calculate the potential economic losses. The results show that the inundated area that occurred in 2030 was 1,718.2 ha with the potential economic losses Rp. 6,130 trillion. With the land subsidence scenario that happen at the area, inundated area increased to 5,171.3 ha with the eonomic potential loss about Rp. 28,724 trillion.